Literasi kesehatan mengenai polusi udara ambien pada mahasiswa kedokteran - Ade, Sherline I; Wang, Charissa; Atmodjo, Wahyuni L; Wijaya, Ratna S (Universitas Kristen Maranatha, 2025)
Ambient (outdoor) air pollution causes worldwide health problem. One of the strategies for reducing ambient air pollution is to increase public participation, which depends on individual ambient air pollution health literacy (AAPHL). Medical professionals, including medical students, require a high level of AAPHL to support adequate health literacy in the community. However, the level of AAPHL of medical students is still unclear, particularly in areas with high levels of ambient air pollution in Indonesia, such as Jakarta and Tangerang. This study aims to evaluate the level and factors associated with AAPHL of medical students. The health literacy of ambient air pollution was assessed using a 24-item AAPHL questionnaire. This study included 107 participants whose mean of age was 19.63. Most participants were female (70%) and third-year medical students (51%). The mean of the total AAPHL scores was 2.85 out of 4. The highest score of competencies was noted for understanding health information, while the lowest was noted for appraising health information. No association between age, gender, and year of study with AAPHL score was found. In conclusion, the AAPHL level among medical students in Indonesia was considered moderate. The low appraising competency of AAPHL indicates a potential area for improvement.